Clinical and genetic spectrum of interstitial lung disease in Chinese children associated with surfactant protein C mutations - Da Hong; Dan Dai; Jing Liu; Congcong Zhang; Tingting Jin; Yanyan Shi; Gaoli Jiang; Mei Mei; Libo Wang; Liling Qian (BMC, 2019)
Abstract Background Mutations in the surfactant protein C gene (SFTPC) result in interstitial lung disease (ILD). Our objective was to characterize clinical and genetic spectrum of ILD in Chinese children associated with SFTPC mutations. Methods Six Chinese children with ILD heterozygous for SFTPC mutations were included. Candidate genes responsible for surfactant dysfunction were sequenced by next-generation sequencing. Subclones of SFTPC with novel mutations were generated and transiently transfected into A549 cells. The functional characterization of mutant surfactant protein C (SP-C) was evaluated by Western blotting and immunofluorescence. Results The age of onset ranged from 7 days to 15 months. All cases required supplemental oxygen. Failure to thrive (5/6) was the most significant extra-pulmonary manifestation. Hydroxychloroquine was given as the long-term treatment of lung disease in four patients and two of them responded well. Three mutations were identified in six patients: four with I73T, one with D105G, one with Y113H. Mutations in three patients were inherited and three arised de novo. Western blotting revealed totally different band patterns between mutant SP-C (D105G and Y113H) and the wildtype. Immunofluorescence showed mutant SP-C (D105G) was scarcely trafficked to lamellar bodies but localized well to early endosomes, which was in marked contrast to the wildtype protein. Conclusion SFTPC mutations were an important cause of childhood ILD in Chinese population. I73T was a common SFTPC mutation in Chinese ILD children associated with surfactant protein C mutations.